Assessment of life status Acer saccharinum in Melitopol - Olshanskya, M. (ТДАТУ, 2018)
EN: The article is devoted to the issues of the stability of the ACER SACCHARINUM species to pollution under conditions of increasing anthropogenic load in urban environment at the example of Melitopol town. The experiments were carried out using the visualization method and by means of V.P. Alekseiev calculation methods. UK: Статтю присвячено питанням стійкості видів ACER SACCHARINUM до забруднення в умовах збільшення антропогенного навантаження на міське середовище на прикладі міста Мелітополь. Експерименти проводилися з використанням візуальної оцінки і за допомогою розрахункового методу В.П Алексєєва.
Keywords: Мелітополь; Melitopol; використання візуальної оцінки; visualization method; Urban vegetation